The best way to discontinue PPIs is still in (re)flux. Issue 6 (June 2015) - Benson, Janice L.
Abstract : N/A: Haastrup P, Paulsen MS, Begtrup LM, Hansen JM, Jarbøl DE. Strategies for discontinuation of proton pump inhibitors: a systematic review. Fam Pract . 2014; 31(6):625–630.